Olaratumab for the treatment of advanced soft tissue sarcoma. Issue 10 (3rd October 2017) - Okuno, Scott H.; Maran, Avudaiappan; Robinson, Steven I.
ABSTRACT: Introduction : Olaratumab, a human monoclonal antibody against platelet derived growth factor receptor alpha (PDGFR- α), is the first drug that in combination with doxorubicin for the treatment of patients with advanced/metastatic soft tissue sarcoma (STS) that has showed an improved overall survival compared to doxorubicin alone. These initial results are exciting and have the potential to change the landscape of treatment for patients with STS. Areas covered : This article reviews the development of olaratumab for oncology use by reviewing articles in PubMed for 'platelet derived growth factor' and 'receptor' and 'soft tissue sarcoma'. We provide an overview of the published studies to date for olaratumab and specifically the use in soft tissue sarcoma. Expert commentary : Olaratumab is a well-tolerated drug that, when combined with doxorubicin, has shown an improved overall survival compared to doxorubicin alone and the phase III confirmatory study is eagerly awaited.